HUBUNGAN GAYA HIDUP DAN RIWAYAT KONTROL DENGAN DERAJAT HIPERTENSI PADA LANSIA - Yulita, Yulita; Zulfitri, Reni; Deli, Hellena (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Aging is a natural process that occurs in the elderly, followed by major diseases are hypertension. Hypertension is an increase in blood pressure above normal, based on the results of blood pressure measurements, hypertensive patients must pay attention to their lifestyle and control history. The purpose of this study was to determine the relationship of lifestyle and control history with the degree of hypertension. This study uses a descriptive correlation research design through aapproach cross sectional. The number of samples of this study were 97 people who were taken using purposive sampling technique by paying attention to inclusion criteria. The measuring instruments used were questionnaires, medical records and sphygmomanometers. The analysis used was univariate analysis with frequency distribution and bivariate with an alternative test, namely Kolmogorov-smirnov, because it did not meet thetest requirements Chi Square. The results showed that there was a significant relationship between physical activity (p value 0.001 < 0.05), diet (p value 0.032 < 0.05), smoking (p value 0.023 < 0.05), alcohol (p value 0.018 < 0.05), stress (p value 0.008 < 0.05), and history of control (p value 0.037 < 0.05) with the degree of hypertension. Based on the results of this study, it is expected that the elderly will make lifestyle changes and routinely control blood pressure in order to reduce the patient's blood pressure. Keywords : Control history, elderly, hypertension degree, lifestyle